Infinitely many sign-changing solutions for a class of critical elliptic systems with Neumann conditions. Issue 1 (30th January 2014) - Filho, D. C. de Morais; Faria, L. F. O.; Miyagaki, O. H.; Pereira, F. R.
<x content-type="archive" xml:space="preserve">Abstract</x> In this work we study the multiplicity results for a class of critical elliptic systems related to the Brézis–Nirenberg problem with the Neumann boundary condition on a ball. Our approach relies on a minimization argument for an auxiliary problem with a mixed boundary condition and on suitable estimates of the critical level for the system case.